2020
DOI: 10.1088/1742-6596/1521/4/042012
|View full text |Cite
|
Sign up to set email alerts
|

Validity of module based on project based learning in media biology subject

Abstract: Media biology subject pushed the students to produce the media that used in learning process, but no one the student used the learning material. It made the student not creative to make the designed or created the media. To solved this problem, it need to develop the learning material based on project based learning, because in media biology subject the students must designed or created the media that used in learning. Module was helped the students learned indenpendently. It made student learned to design and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
1
7
0
2
Order By: Relevance
“…Students rated the first item which refer to the pictures and drawings of the module are both familiar to the learner as the lowest mean score of 3.84 (SD = 0.95) with a verbal description of high. The result corroborates the study of Susanti et al [21] wherein the language aspects of the module that they designed have the following: module's letter form and size are readable, the information is clearly presented, the language used is correct and appropriate, and the module's readability and clarity of information were unquestionable. In their study, the development of the modules was found to be beneficial in making the learning process easier for the students to carry out.…”
Section: Presentationsupporting
confidence: 87%
See 1 more Smart Citation
“…Students rated the first item which refer to the pictures and drawings of the module are both familiar to the learner as the lowest mean score of 3.84 (SD = 0.95) with a verbal description of high. The result corroborates the study of Susanti et al [21] wherein the language aspects of the module that they designed have the following: module's letter form and size are readable, the information is clearly presented, the language used is correct and appropriate, and the module's readability and clarity of information were unquestionable. In their study, the development of the modules was found to be beneficial in making the learning process easier for the students to carry out.…”
Section: Presentationsupporting
confidence: 87%
“…Richards [20]] mentioned that there are lessons in the modules for which students lack prior knowledge; however, since the material is presented efficiently and logically, students easily understand the topic. Moreover, according to Susanti et al [21] effective sentences are ones that are free from ambiguity. Less effective sentences will lead to students getting confused about the module's content.…”
Section: Communication Stylementioning
confidence: 99%
“…Students will be more passionate about reading comics with visual pictures and storylines that catch their attention and engage their thoughts than they would be about reading textbooks in the form of books given by the government (Febriansyah et al, 2020;Sopacua et al, 2020). Continuous comic pieces combine to form a coherent and inseparable whole, allowing the viewer to comprehend the complete contents of the depicted comic (Susanti et al, 2020). Popular comics are commonly adapted into anime so that, in addition to 2-dimensional representation, comic readers may now see comic material in 3 dimensions or more realistically, rather than merely envisioning it via each person's imagination (Hwang et al, 2020).…”
Section: The Results Of Observing the Completeness Of Comic Elementsmentioning
confidence: 99%
“…Biology is one of the compulsory subjects for high school students in Indonesia [1]. The main focus of biology subjects is to teach science teaching materials as provisions for students in real life in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its characteristics, biology subjects adhere to the philosophy of realism education, where the learning process will be more effective if students can directly observe the values of the subject objects that can be seen now [4], so biology learning requires learning media that are can be seen directly by the students. Therefore, every biology teacher should ideally have various abilities in implementing classroom management [5], as well as developing relevant biology teaching materials [1], so that learning objectives can be achieved effectively efficiently [6]. The ability of biology teachers to develop effective elearning teaching materials is more needed in the era of the Covid-19 pandemic because learning during the Covid-19 pandemic, the majority of which was carried out online (distance learning).…”
Section: Introductionmentioning
confidence: 99%